Experimental Analysis and Performance Evaluation of Spider Hydraulic Buffer for Rod Dropping in Reactor - Yue, Ti; Yuan, Pan; Huang, Shan; Zhu, Fawen; Li, Yuanming; Huang, Chunlan; Zheng, Lele; Wang, Haoyu; Liu, Menglong (Frontiers in Energy Research, 2022)
Control rod drop is one of the key measures for the safe shutdown of the reactor. The two important evaluation indicators of the drop process are the drop time-length and the maximum impact force. By theoretical and experimental methods, this paper analyzes the influencing factors and evaluates the performance of a new type of spider hydraulic buffer with compact structure and ingenious design, which couples mechanical force and fluid resistance. First, through experiments, it is found that the real-time curve of the maximum impact force often has a bimodal structure. And the double peaks vary with the change of the internal structure of the hydraulic buffer. Secondly, since there are many variables about the structure (aperture, position, quantity, piston stroke et al.), in order to consider their influence on the maximum impact force, an equivalent ongoing flow area of the drain holes is introduced. It suggested that when the flow area of the working holes which can be covered by the stroke is close to the flow area of the remaining holes, the impact force tends to appear a minimum value. A relationship between the maximum impact force and the structure is proposed accordingly. Finally, this paper proposes a quantitative evaluation method for comprehensive buffering performance, in which the comprehensive performance evaluation factor η (0<η<1) takes into account both the maximum impact force and the drop time. The smaller the maximum impact force and the rod drop time-length, the closer the evaluation factor η is to 1, indicating that the buffering performance is better. The research in this paper will not only help to further understand the mechanism of the drop rod buffering process, but also contribute to the structural optimization of the subsequent spider hydraulic buffer.